(untitled) - I M Crawford (Rome, Italy, 1997)
This book reviews the roleof marketing research and the techniques used to undertake market research, including questionnaire design and sampling and writing of a research report. It dalso discusses the principal components of a marketing information system and the use of marketing research information in decision-making
Keywords: agriculture - economic aspects,farm produce,marketing